High frequency weldable polyolefin composition
Patent Information
- Application Number
- CN202280077800.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-03
- Filing Date
- 2022-11-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-11-24
AI Technical Summary
然而,这些应用不允许用高频焊接焊接纯聚烯烃制品
Smart Images

Figure BDA0004854285950000081 
Figure BDA0004854285950000121 
Figure BDA0004854285950000131
Abstract
Description
Technical Field
[0001] This invention relates to the field of welding polyolefin articles. More specifically, this invention relates to polyolefin compositions that can be welded by dielectric heating, wherein articles made from said compositions exhibit good printability, sealing properties, and good sealing strength. Background Technology
[0002] High-frequency (HF) welding, also known as dielectric sealing or radio-frequency (RF) heat sealing, is a well-established technology known since the 1940s. HF welding is fast and relatively easy to perform, produces only limited polymer degradation even when welding thick layers, generates no fumes, requires a moderate amount of energy, and can produce welds that are waterproof, airtight, and antibacterial.
[0003] High-frequency welding provides a non-contact, direct, volumetric heating method for dielectric materials defined as those capable of absorbing electromagnetic energy and being very poor electrical conductors. This is achieved by applying an alternating electric field generated within a given frequency range to the dielectric material. The dielectric loss factor, also known as the dielectric loss index, is a measure of a material's energy loss and indicates the degree to which the material is heated in a high-frequency alternating electric field. If a material has a relatively high dielectric loss index, it may be well-suited for dielectric heating. In this case, dielectric heating offers a clean and controlled process, eliminating the problems associated with directly heating various materials. Therefore, this process has been found to be economically attractive for use in certain commercial and industrial manufacturing processes. Dielectric heating is typically performed using radio frequency (RF) waves (3 kHz to 300 GHz), which includes microwaves (300 MHz to 300 GHz). These bands are referred to as high-frequency (HF) waves.
[0004] In high-frequency (HF) welding or sealing, to create a seal, at least one surface of a sheet or film of the aforementioned suitable material is welded or sealed to another surface of the same sheet or another sheet or film. The resulting weld can be as strong as the original material. This process involves placing the components to be joined in a high-frequency electromagnetic field, typically applied between two metal rods. These rods also act as pressure applicators during heating and cooling. The dynamic electric field causes the molecules in polar thermoplastics to oscillate. Depending on their geometry and dipole moment, these molecules convert oscillatory kinetic energy into heat energy, causing the material to heat up.
[0005] The most prominent polymer that can be used for high-frequency welding is polyvinyl chloride (PVC). However, chlorides can pose environmental or toxic challenges that manufacturers wish to avoid.
[0006] Therefore, finding a method to manufacture normal, lossless materials such as polyolefins suitable for high-frequency welding has been an ongoing research topic. One approach is to add a certain proportion of a second radio frequency responsive material to it.
[0007] WO 2002 / 088229 discloses a dielectric heating thermoplastic composition comprising the addition of a molecular sieve having at least one copolymer, the copolymer comprising (i) polymer units derived from at least one aliphatic olefin monomer containing 2 to 20 carbon atoms; and (ii) polymer units derived from (a) at least one vinyl or vinylidene aromatic monomer, or (b) derived from at least one sterically hindered aliphatic or alicyclic vinyl or vinylidene monomer, or (c) polymer units derived from a combination of at least one vinyl or vinylidene aromatic monomer and at least one sterically hindered aliphatic or alicyclic vinyl or vinylidene monomer; and optionally, (d) polymer units derived from at least one olefinically unsaturated polymerizable monomer rather than from (a), (b), and (c). Ethylene-styrene copolymers are an example.
[0008] JP-A-10-219048 describes a high-frequency weldable polypropylene composition consisting of fine metal oxide particles, ion-substituted zeolite, and polypropylene. In the ion-substituted zeolite, some or all exchangeable ions are replaced by ammonium and silver ions, serving as nucleating agents and chlorine scavengers.
[0009] EP 193 902 proposes the use of zinc oxide, bentonite clay, or crystalline and amorphous alkali or alkaline earth metal aluminosilicates as high-frequency sensitizers for high molecular weight, high-density polyethylene, or ultra-high molecular weight polyethylene. It teaches that the radio frequency sensitizer must be substantially dry before use.
[0010] However, these attempts all have the drawback of incorporating materials into the composition, which is unnecessary for the properties of the composition itself. Therefore, attempts have been made to incorporate dipole properties directly into the polymer.
[0011] EP 0149782 discloses a composition comprising silane-grafted polyolefin and crystalline zeolite. The composition can be molded into articles, which, after molding, can be exposed to humidity and / or microwave crosslinking. KR 2005 0017153(A) provides a polyvinyl resin composition using an ethylene-vinyl acetate copolymer and an ethylene-glycidyl methacrylate copolymer, particularly (A) 30-70 parts by weight of high-density polyethylene resin with a density of 0.935-0.965 g / cm³. 3The following are further attempts: (A) 30-40 parts by weight of an ethylene-vinyl acetate copolymer, wherein the vinyl acetate content is 30-40 parts by weight and the melt index is 3-10 g / 10 min; and (C) 10-20 parts by weight of an ethylene-glycidyl methacrylate copolymer, wherein the glycidyl methacrylate content is 30-40 parts by weight. See UK 2 177 974 for further attempts to provide high-frequency weldable compositions based on the combination of polyolefins and vinyl acetate. WO 94 / 12569 discloses the use of blends of propylene-ethylene copolymers and ethylene-alkyl acrylate copolymers for high-frequency welding. Further attempts are based on carbon monoxide-based monomers (WO 00 / 69629) and polyamides (US 3 336 173). In addition to the general problem that it is impossible to process pure polyolefin materials, ethylene and vinyl acetate used in the prior art are known to have poor mechanical properties in some applications involving high-frequency welding.
[0012] Other attempts have been made to prepare films with different layers, wherein at least one layer has dielectric properties suitable for high-frequency welding, and the other layers are polyolefins that receive heat from other layers during high-frequency welding, i.e., in sandwich structures, see JP 2003 320583(A) and JP S 59184611(A). However, these applications do not allow for the welding of pure polyolefin articles using high-frequency welding. Summary of the Invention
[0013] Purpose of this invention
[0014] Therefore, given the aforementioned issues, there remains a need for polymer compositions suitable for high-frequency welding that avoid the direct processing limitations of chlorinated materials such as PVC (i.e., without the aid of other materials such as molecular sieves or auxiliary layers in membranes), while possessing good sealing strength and printability. In particular, there is a need for such polymer compositions capable of forming high-frequency weldable structures, including, for example, films, sheets, foams, profiles, fibers, molded parts, or articles.
[0015] Overview of the Invention
[0016] It has been surprisingly discovered that the above objective can be achieved by a crosslinkable polyethylene composition for high-frequency welding, the composition comprising:
[0017] - A copolymer (A) of ethylene and an α-olefin comonomer (A1) having 3 to 12 carbon atoms, with a density of 850 kg / m³. 3 Up to 970kg / m 3 ,as well as
[0018] - A terpolymer (B) of ethylene, a polar comonomer (B1), and a crosslinkable comonomer (B2).
[0019] It has been further discovered that the above objective can be achieved by articles suitable for high-frequency welding containing the crosslinkable polyethylene composition.
[0020] It was further discovered that the above-mentioned objective can be achieved by using the crosslinkable polyethylene composition for high-frequency welding. Detailed Implementation
[0021] This invention relates to a crosslinkable polyethylene composition for high-frequency welding, comprising:
[0022] - A copolymer (A) of ethylene and an α-olefin comonomer (A1) having 3 to 12 carbon atoms, with a density of 850 kg / m³. 3 Up to 970kg / m 3 ,as well as
[0023] - A terpolymer (B) of ethylene, a polar comonomer (B1), and a crosslinkable comonomer (B2).
[0024] The sealing time of the crosslinkable polyethylene composition is preferably less than 7 seconds, more preferably less than 6 seconds, and most preferably less than 5 seconds.
[0025] The sealing strength of the crosslinkable polyethylene composition is preferably at least 1.0 N / mm. 2 Preferably at least 1.5 N / mm 2 More preferably at least 3N / mm 2 The optimal value is at least 4.5 N / mm. 2 .
[0026] Therefore, the composition is preferably prepared by compounding the two polymers (A) and (B) in an extruder. The two polymers will be described in more detail below.
[0027] Preferably, the total amount of polymers (A) and (B) in the composition is greater than or equal to 90 wt% relative to the total weight of the composition, more preferably greater than or equal to 95 wt%, and most preferably greater than or equal to 98 wt%.
[0028] Also preferably, the weight ratio of polymer (A) to polymer (B) in the composition is preferably in the range of 75:25 to 25:75, more preferably 50:30 to 30:60, and most preferably 55:45 to 45:55.
[0029] As used herein, the term "high-frequency welding" refers to a method of non-contact, direct, volumetric heating of a polymer by applying an alternating electric field generated within a given frequency range to the polymer. This method typically utilizes a frequency range of 3 kHz to 300 MHz, preferably 10 kHz to 200 MHz, more preferably 20 MHz to 200 MHz, even more preferably 25 MHz to 72 MHz, and most preferably 27 MHz.
[0030] Ethylene copolymer (A)
[0031] The crosslinkable polyolefin compositions of the present invention comprise ethylene and C3 to C4 olefins. 12 A copolymer of α-olefin comonomers (A).
[0032] The copolymer (A) can include high-density, medium-density, low-density, and even very low-density ethylene copolymers. According to ISO 1183-1:2004, its density is preferably 850 kg / m³. 3 Up to 970kg / m 3 Within the range, 860 kg / m² is more preferred. 3 Up to 930kg / m 3 Even more preferred is 860 kg / m 3 Up to 915kg / m 3 The optimal value is 880 kg / m³. 3 Up to 910 kg / m 3 .
[0033] The MFR of copolymer (A) was determined according to ISO 1133. 2.16 The preferred concentration is 0.1 g / 10 min to 50 g / 10 min, more preferably 0.5 g / 10 min to 25 g / 10 min, even more preferably 0.7 g / 10 min to 15 g / 10 min, and most preferably 1.0 g / 10 min to 10 g / 10 min.
[0034] The copolymer (A) is preferably ethylene with C3 to C4. 12 A copolymer of α-olefin comonomers, more preferably a copolymer of α-olefin comonomers having C3 to C4 atoms. 10 Comonomers of α-olefins, such as propylene, 1-butene, 1-hexene, 1-octene, and 1-decene, and even more preferably having C4 to C5 atoms. 10 The copolymer (A) is a comonomer of α-olefins, and more preferably a comonomer of α-olefins having C7 to C9. Most preferably, copolymer (A) is a copolymer of ethylene and 1-octene. The density of the ethylene and 1-octene copolymer, as determined according to ISO 1183-1:2004, is preferably 850 kg / m³. 3 Up to 930kg / m 3Within the range, more preferably within 855 kg / m 3 Up to 920kg / m 3 Within the range, or even preferably within 870 kg / m 3 Up to 910 kg / m 3 Within the range.
[0035] The ethylene copolymer (A) preferably has a DSC peak melting point of 65°C to 85°C as determined according to ISO 11357, and more preferably 70°C to 80°C.
[0036] More preferably, copolymer (A) is ethylene and C3 to C4. 12 The most preferred copolymer is a binary copolymer of α-olefin comonomers, wherein copolymer (A) is a binary copolymer of ethylene and 1-octene.
[0037] Preferably, ethylene-1-butene or ethylene-1-octene copolymers (plastics) can be used. Any copolymer of ethylene and 1-butene or 1-octene having the above-described properties can be used. Preferred materials are commercially available, for example, materials from Borealis under the trade name Queo, materials from DOW Chemical Corp (USA) under the trade names Engage or Affinity, or materials from Mitsui Chemicals under the trade name Tafmer.
[0038] Alternatively, these plastics can be prepared by known processes, including solution polymerization, slurry polymerization, gas-phase polymerization, or combinations thereof in a one- or two-step polymerization process, in the presence of a suitable catalyst, such as vanadium oxide catalysts or single-center catalysts well known to those skilled in the art, for example, metallocene or geometrically confined catalysts. Preferably, a metallocene catalyst is used.
[0039] Preferably, these plastites are prepared by one-step or two-step solution polymerization, particularly by high-temperature solution polymerization at temperatures above 100°C.
[0040] This process is essentially based on polymerizing monomers and suitable comonomers in a liquid hydrocarbon solvent, the resulting polymer being soluble in the solvent. The polymerization reaction is carried out at a temperature above the polymer's melting point, thus yielding a polymer solution. This solution is flash-evaporated to separate the polymer from the unreacted monomers and solvent. The solvent is then recovered and recycled within the process.
[0041] Solution polymerization is preferably carried out at a high-temperature solution polymerization temperature above 100°C. More preferably, the polymerization temperature is at least 110°C, and even more preferably at least 150°C. The polymerization temperature can be as high as 250°C.
[0042] In this solution polymerization process, the pressure is preferably in the range of 10 bar to 100 bar, more preferably 15 bar to 100 bar, and even more preferably 20 bar to 100 bar. The liquid hydrocarbon solvent used is preferably C24-442 ... 5-12 Hydrocarbons, which may be unsubstituted or C-substituted. 1-4 Alkyl-substituted, such as pentane, methylpentane, hexane, heptane, octane, cyclohexane, methylcyclohexane, and hydrogenated naphtha. More preferably, unsubstituted C4 is used. 6-10 Hydrocarbon solvent.
[0043] The known solution technology suitable for the process of this invention is Borceed. TM technology.
[0044] Ethylene terpolymer (B)
[0045] The ethylene terpolymer (B) contains a polar comonomer unit (B1) and a crosslinkable comonomer unit (B2).
[0046] The ethylene terpolymer (B) may comprise one or more crosslinkable ethylene copolymers containing both comonomer units (B1) and (B2), or may consist of one or more crosslinkable ethylene copolymers containing both comonomer units (B1) and (B2). It may also comprise a mixture of different polymers, or a mixture of different polymers containing ethylene copolymers containing either comonomer unit (B1) or comonomer unit (B2), or both comonomer units (B1) and (B2). However, regardless of the polymer used, the ethylene terpolymer (B) must contain an ethylene copolymer such that both comonomer units (B1) and (B2) are present in component (B).
[0047] Preferably, the ethylene terpolymer (B) comprises one or more crosslinkable ethylene copolymers containing comonomer units (B1) and (B2), or is composed of one or more crosslinkable ethylene copolymers containing comonomer units (B1) and (B2). More preferably, the ethylene terpolymer (B) comprises a crosslinkable ethylene copolymer containing comonomer units (B1) and (B2), or is composed of a crosslinkable ethylene copolymer containing comonomer units (B1) and (B2). Most preferably, the ethylene terpolymer (B) is composed of a crosslinkable ethylene copolymer containing comonomer units (B1) and (B2).
[0048] Preferably, in a preferred embodiment of the ethylene terpolymer (B) comprising one or more (preferably one) ethylene copolymers containing comonomer units (B1) and (B2), the amount of the one or more (preferably one) ethylene copolymers containing comonomer units (B1) and (B2) is at least 10 wt%, preferably at least 15 wt%, of the total amount of the ethylene terpolymer (B).
[0049] Ethylene copolymers having comonomer units (B1) and (B2) are preferably obtained by copolymerization of ethylene, a polar comonomer unit (B1), and a comonomer unit (B2) having a hydrolyzable group. The copolymerization of ethylene, the polar comonomer unit (B1), and the comonomer unit (B2) having a hydrolyzable group can be carried out under any suitable conditions under which monomer copolymerization occurs.
[0050] Ethylene terpolymers containing (B1) and (B2) comonomer units can be prepared by free radical-initiated high-pressure polymerization. Generally, the copolymerization reaction of the above monomers is carried out in a polymerization reactor in the presence of a free radical initiator at a temperature of approximately 100°C–300°C and a pressure of approximately 100 MPa–300 MPa. Typically, the polymerization reaction is carried out continuously, preferably in a tubular reactor or an autoclave reactor.
[0051] Ethylene copolymers having (B1) and (B2) comonomer units can also be prepared by grafting, for example, using the methods described in US 3,646,155 and US 4,117,195. However, it is preferred to prepare ethylene copolymers having (B1) and (B2) comonomer units via the copolymerization reaction described herein, rather than by grafting. In other words, ethylene copolymers having (B1) and (B2) comonomer units are preferably ungrafted ethylene copolymers having (B1) and (B2) comonomer units.
[0052] The ethylene copolymer having (B1) and (B2) comonomer units can be pre-produced or produced in a reactor. Pre-produced refers to a commercially available ethylene copolymer. Preferably, the pre-produced ethylene copolymer is a blend of two or more different ethylene copolymers, more preferably a blend of two different ethylene copolymers.
[0053] However, ethylene copolymers having (B1) and (B2) comonomer units are preferably prepared in a reactor. Preferably, the reactor is a tubular reactor.
[0054] Preferably, the amount of polar comonomer (B1) in the ethylene terpolymer (B) is 10 wt% to 35 wt%, more preferably 15 wt% to 34 wt%, even more preferably 17 wt% to 33 wt%, even more preferably 20 wt% to 32 wt%, and most preferably 25 wt% to 30 wt%.
[0055] Preferably, the polar comonomer (B1) is selected from (C1-C6)-alkyl acrylates and (C1-C6)-alkyl acrylates. More preferably, the polar comonomer (B1) is selected from methyl acrylate, ethyl acrylate, and / or butyl acrylate. Among them, methyl acrylate (MA) is the most preferred.
[0056] Preferably, the MFR2 (2.16 kg / 190 °C) of the ethylene terpolymer (B) is in the range of 0.1 g / 10 min to 50 g / 10 min, as determined according to ISO 1133, and more preferably in the range of 25 g / 10 min to 35 g / 10 min.
[0057] Crosslinking of ethylene copolymers with polar comonomer units and crosslinkable comonomer units is well known in the art and can be carried out by so-called moisture curing, see, for example, WO00 / 68314. A silanol condensation catalyst is used as the catalyst.
[0058] The advantage of producing ethylene copolymers with (B1) and (B2) comonomer units in the reactor is that they can be directly used in subsequent steps of the process of this invention.
[0059] Preferably, the amount of crosslinkable comonomer (B2) in the ethylene copolymer composition (B) is 0.1 wt% to 6 wt%, more preferably 0.2 wt% to 5.5 wt%, even more preferably 0.3 wt% to 5 wt%, and most preferably 0.4 wt% to 4.5 wt%.
[0060] Preferably, the crosslinkable comonomer unit (B2) is a comonomer unit having a hydrolyzable silane group.
[0061] Therefore, preferably, the crosslinkable comonomer unit (B2) is represented by formula (I):
[0062] R 1 SiR 2 q Y 3-q (I)
[0063] Among them, R 1 It is an olefinic unsaturated hydrocarbon group, alkyloxy group, or (meth)acryloyloxy hydrocarbon group.
[0064] Each R 2It is independently an aliphatic saturated hydrocarbon group.
[0065] Y can be the same or different, and can be a hydrolyzable organic group.
[0066] q can be taken from 0, 1, or 2.
[0067] If multiple Y groups are present, they do not have to be the same.
[0068] Specific examples of crosslinkable comonomer units (B2) are: R1 is vinyl, allyl, isopropenyl, butenyl, cyclohexenyl, or γ-(meth)acryloyloxypropyl; Y is methoxy, ethoxy, formoxy, acetoxy, propionyloxy, or alkyl or aromatic amino; and, if present, R 2 It can be methyl, ethyl, propyl, or decyl.
[0069] The preferred crosslinkable comonomer (B2) is represented by formula (II):
[0070] CH2=CHSi(OA)3(II)
[0071] Wherein, A is a hydrocarbon group having 1-8 carbon atoms, preferably 1-4 carbon atoms.
[0072] Most preferably, the crosslinkable comonomer (B2) includes vinyltrimethoxysilane (VTMS), vinylbismethoxyethoxysilane, vinyltriethoxysilane, γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, vinyltriacetoxysilane, and combinations thereof.
[0073] Silanol condensation catalyst (C)
[0074] In a preferred embodiment of the invention, the crosslinkable polyethylene composition further includes a silanol condensation catalyst (C).
[0075] Preferably, the silanol condensation catalyst (C) comprises a tin-based catalyst or a sulfonic acid-based catalyst, or is composed of a tin-based catalyst or a sulfonic acid-based catalyst, more preferably comprising a sulfonic acid-based catalyst or is composed of a sulfonic acid-based catalyst. The tin-based catalyst is preferably dibutyltin dilaurate (DBTL).
[0076] Sulfonic acid-based catalysts are preferably represented by formula (III):
[0077] ArSO3H(III)
[0078] Or its precursor, Ar is a benzene ring substituted with at least one hydrocarbon radical having a total carbon number of 8-20, or a naphthalene ring substituted with at least one hydrocarbon radical having a total carbon number of 4-18, and the catalyst of formula (III) contains a total of 14-28 carbon atoms. Unlike conventional silanol condensation catalysts such as DBTL, this catalyst allows crosslinking at ambient temperatures such as room temperature.
[0079] Such organic sulfonic acids are described, for example, in EP 736 065, or alternatively in EP 1 309 631 and EP 1309 632.
[0080] Preferably, based on the total amount of the polyethylene composition, the amount of silanol condensation catalyst (C) is 0.00015 wt% to 0.045 wt%, or 0.00000044 mol% to 0.00013 mol%.
[0081] If a masterbatch containing the catalyst is used, the amount used is preferably 0.01 wt% to 8 wt%, more preferably 0.5 wt% to 7 wt%, and most preferably 0.1 wt% to 6 wt% based on the total polyethylene composition.
[0082] In addition to the base resin, common additives used in polyolefins, such as pigments, stabilizers (antioxidants), acid stabilizers and / or UV stabilizers, antistatic agents, and application agents (such as processing aids), may also be present in the polyethylene composition. Preferably, the amount of these additives is 10 wt% or less of the total composition, more preferably 8 wt% or less, even more preferably 5 wt% or less, and even more preferably 4 wt% or less.
[0083] The present invention further provides a crosslinkable polyethylene composition that can be obtained by the above method.
[0084] The present invention also provides an article suitable for welding, comprising, or consisting of, a crosslinkable polyethylene composition, or consisting of a crosslinkable polyethylene composition according to the present invention.
[0085] Preferably, the article is a seal or membrane, particularly a waterproof tarpaulin, strip, skylight, tent, and / or geotextile.
[0086] Finally, the present invention relates to the use of the crosslinkable polyethylene composition according to the present invention for high-frequency welding.
[0087] Experimental Section
[0088] Determination methods
[0089] a) Melt flow rate
[0090] Melt flow rate (MFR) is determined according to ISO 1133, with units of g / 10 min. MFR is an indicator of polymer melt viscosity. The MFR of polyethylene is measured at 190°C, and that of polypropylene at 230°C. The load used to measure melt flow rate is usually expressed with a subscript; for example, MFR2 is measured at a load of 2.16 kg (condition D).
[0091] b) Density
[0092] The density of the polymer is measured according to ISO 1183 / 1872-2B. For the purposes of this invention, the density of the blend can be calculated from the density of each component according to the following formula:
[0093]
[0094] in
[0095] ρ b It is the density of the blend.
[0096] w i It is the weight fraction of component 'i' in the blend, and
[0097] ρ i It is the density of component 'i'.
[0098] c) Quantification of microstructure by NMR spectroscopy
[0099] The content (wt% and mol%) of polar comonomers present in the polymer and the content (wt% and mol%) of silane-containing units (preferably comonomers) present in the polymer composition (preferably in the polymer):
[0100] As described above or below, quantitative nuclear magnetic resonance (NMR) spectroscopy is used to quantify the content of comonomers in polymer compositions or polymers.
[0101] A Bruker Advance III 400 NMR spectrometer was used, and the operation was performed at 400.15 MHz. Quantitative data were recorded in solution. 1¹H NMR spectroscopy. Nitrogen was used for all pneumatic processes, and all spectra were recorded at 100 °C using a standard broadband reverse 5 mm probe. Approximately 200 mg of material was dissolved in 1,2-tetrachloroethane-d2 (TCE-d2) using di-tert-butylhydroxytoluene (BHT) (CAS128-37-0) as a stabilizer. Standard single-pulse excitation was used with a 30° pulse, a 3-second relaxation delay, and no sample rotation. Two virtual scans were performed, acquiring 16 transients for each spectrum. A total of 32 k data points were collected per FID with a residence time of 60 μs, corresponding to a spectral window of approximately 20 ppm. The FIDs were then zero-filled to 64 k data points, and an exponential window function with 0.3 Hz line broadening was applied. This setup was chosen primarily to resolve quantitative signals generated by the copolymerization of methacrylate and vinyltrimethylsiloxane in the same polymer.
[0102] Quantitative analysis was performed using a customized automated spectral analysis program. 1 ¹H NMR spectral processing, integration, and determination of quantitative properties. All chemical shifts were internally referenced to a residual protonated solvent signal of 5.95 ppm.
[0103] When characteristic signals are observed from the sequential incorporation of vinyl acetate (VA), methyl acrylate (MA), butyl acrylate (BA), and vinyltrimethylsiloxane (VTMS) in different comonomer sequences... [1] The content of all comonomers is calculated relative to all other monomers present in the polymer.
[0104] The introduction of vinyl acetate (VA) was quantified using the integral of the signal assigned to the *VA site at 4.84 ppm as a percentage of the number of reporting nuclei per comonomer, and corrected for overlap of OH protons in the presence of BHT.
[0105] VA = (I *VA –(I ArBHT ) / 2) / 1
[0106] The introduction of methyl acrylate (MA) was quantified using the integral of the signal assigned to the 1MA site at 3.65 ppm as a percentage of the number of reporter cores per comonomer:
[0107] MA=I 1MA / 3
[0108] The introduction of butyl acrylate (BA) was quantified using the integral of the signal assigned to the 4BA site at 4.08 ppm as a percentage of the number of reporter cores per comonomer:
[0109] BA = I 4BA / 2
[0110] The introduction of vinyltrimethylsiloxane (VTMS) was quantified using the integral of the signal assigned to 1 VTMS site at 3.56 ppm as a percentage of the number of reporter cores per comonomer:
[0111] VTMS = I 1VTMS / 9
[0112] Characteristic signals were observed due to the additional use of BHT as a stabilizer. BHT content was quantified using the integral of the signal assigned to the ArBHT site at 6.93 ppm as a percentage of the number of reporter cores per comonomer.
[0113] BHT=I ArBHT / 2
[0114] The content of ethylene comonomers was quantified using a bulk aliphatic (bulk) signal integral in the range of 0.00–3.00 ppm. This integral may include 1VA(3) and αVA(2) sites introduced from vinyl acetate (VA) alone, *MA and αMA sites introduced from methyl acrylate alone, 1BA(3), 2BA(2), 3BA(2), *BA(1), and αBA(2) sites introduced from butyl acrylate alone, *VTMS and αVTMS sites introduced from vinyl silane alone, aliphatic sites from BHT, and sites from the polyethylene sequence. The total content of ethylene comonomers was calculated based on the bulk integral, with compensation for observed comonomer sequences and BHT.
[0115] E = (1 / 4) * [I] bulk -5*VA-3*MA-10*BA-3*VTMS-21*BHT]
[0116] It should be noted that half of the α signal in the bulk signal represents ethylene rather than the comonomer, and a non-significant error is introduced because it cannot compensate for the two saturated chain ends (S) that do not have associated branching sites.
[0117] The total mole fraction of a given monomer (M) in a polymer is calculated as follows:
[0118] fM = M / (E + VA + MA + BA + VTMS)
[0119] The molar percentage of total monomers introduced into a given monomer (M) is calculated using the standard method based on molar fraction:
[0120] M[mol-%]=100*fM
[0121] The weight percentage of total monomers introduced into a given monomer (M) is calculated using the standard method from the mole fraction and molecular weight (MW) of the monomers:
[0122] M[wt.-%]=100*(fM*MW) / ((fVA*86.09)+(fMA*86.09)+(fBA*128.17)+(fVTMS*148.23)+((1-fVA-fMA-fBA-fVTMS)*28.05))
[0123] References:
[0124] [1] J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201.
[0125] If characteristic signals are observed from other specific chemical substances, the logic for quantization and / or compensation can be extended in a similar manner to that of the specific chemical substance being described. That is, characteristic signals are identified, quantized by integrating one or more specific signals, the number of reporting cores is scaled, and compensation is performed in the ontological integral correlation calculation. Although this method is specific to the particular chemical substance in question, it is based on the fundamental principles of quantitative NMR spectroscopy of polymers and can therefore be implemented by those skilled in the art as needed.
[0126] d) Sealing strength
[0127] The membrane was welded using a Forstrom High Frequency AB TX-type HF welding machine. The production line was 1200kW, with sealing rods measuring 1200×25mm. The sealing pressure for polyolefin was 4 bar (2 kg / cm), and for PVC, it was 2 bar (CE1). The base tape of the HF welding rod was covered with PTFE tape.
[0128] Measurement of the sealing strength of ultrasonically welded samples;
[0129] The analysis was performed on a tensile testing apparatus according to ISO 527-1. A 25.4 mm wide specimen was cut from the sample and mounted, with the seal located in the center of the clamp. The following settings were used: gauge length 10 mm, preload 0.25 N for 20 seconds, test speed 100 mm / min, and fracture detection at 75% Fmax.
[0130] e) Surface energy and dyne retention
[0131] According to ASTM D2578-09, surface energy is determined by wetting tension using a test ink (a mixture of formamide and ethyl solvent) with a surface tension between 34 dynes / cm and 56 dynes / cm, provided by the AFS Corona Treatment Tester from Augsburg, Germany.
[0132] Importantly, the surface area being tested must not be rough before wetting; it should be as smooth as possible.
[0133] Apply ink to a 6.5cm area using a cotton swab. 2 On the surface, starting with an ink of low surface tension until the applied ink no longer wets the surface, the surface tension is then visually determined by estimating the liquid's reaction within the first two seconds after the ink is applied to the surface. The test liquid can either contract and / or form small spheres (single droplets) or remain unchanged, forming an ink film on the test membrane. When the test liquid contracts or forms droplets, it indicates that the surface energy of the film is lower than that of the applied liquid.
[0134] The test should be repeated multiple times as needed, with the surface tension value of the test ink differing from the first measured dyne value by + / - 2 dynes / cm, until the mark remains stable for two seconds or longer. Once this is achieved, the membrane can be said to have a level or surface energy at least equal to that of the applied liquid.
[0135] Further application should be performed until contraction or droplet formation occurs within two seconds. The final measurement should be considered a failure, and the surface energy of the liquid used in the previous measurement should be considered the surface energy of the membrane.
[0136] The surface tension of the present invention and the comparative embodiment was tested after 8 months of aging.
[0137] Implementation
[0138] Material
[0139] A1 is a very low-density copolymer of polyethylene and 1-octene, with a density of 883 kg / m³. 3 The MFR2 (2.16 kg, 190 °C) is 1.09 g / 10 min, with a peak melting point of 73 °C. Its commercial name is Queo8201, and it is commercially available from Borealis AG (Austria).
[0140] A2 is a very low-density copolymer of polyethylene and 1-octene, with a density of 883 kg / m³. 3 The MFR2 (2.16 kg, 190 °C) is 1.1 g / 10 min, with a peak melting point of 75 °C. Its commercial name is Queo8201LA, and it is commercially available from Borealis AG (Austria).
[0141] B1 is produced in a commercial high-pressure tubular reactor with a density of 926 kg / m³. 3 Poly(ethylene-co-butyl acrylate) with an MFR2 of 4 g / 10 min, an acrylate content of 27 wt%, and a Tm of 90 °C.
[0142] B2 is a terpolymer of ethylene, methyl acrylate and vinyltrimethoxysilane (VTMS) obtained according to the process described in WO 2018 / 171951 A1, having 30 wt% methyl acrylate and 2.23 wt% VTMS, with MFR2 (2.16 kg, 190 °C) at 29 g / 10 min and MFR5 (5 kg, 190 °C) at 99 g / 10 min.
[0143] C1 is Ambicat LE4476, which is dodecylbenzenesulfonic acid (DBSA) used as a catalyst for silanol condensation. It is commercially available from Borealis AG (Austria).
[0144] complex
[0145] The film containing the polymer composition according to the embodiments was prepared by dry mixing the components using the weight percentages given in Table 2 and immediately extruding them on a Reifenhauser cast film production line using the parameters provided in Table 1.
[0146] Table 1
[0147]
[0148]
[0149] For sealing films, PET tape is used to more accurately measure the film's sealing strength to avoid stretching. The film in this embodiment is highly elastic, and to avoid excessive stretching, PET tape is applied to the outside of the high-frequency sealing film before testing the sealing strength.
[0150] Table 2
[0151]
[0152]
[0153] *Seal not completed
[0154] +Measured after eight months of aging. Between extrusion and high-frequency welding: 6 months; between high-frequency welding and testing: 2 months.
[0155] Comparative example CE1 uses common PVC, which results in a fast sealing time, but the sealing strength is not very good.
[0156] Comparative examples CE4-6 demonstrate good sealing properties of acrylate-containing polyethylene, but still exhibit low dyne retention values. CE6 shows that compositions using only terpolymers have immediate crosslinking issues when combined with silanol condensation catalysts. Nevertheless, CE6 still shows good dyne retention.
[0157] It can be further seen that samples with pure A1 or A2 require sealing equipment with higher power and longer sealing time.
[0158] The use of crosslinkable terpolymers blended with ethylene plasmons offers advantages such as sealing on high-frequency welding machines and the absence of immediate crosslinking (i.e., samples require more than eight months of moisture crosslinking). Furthermore, dyne retention is improved. Therefore, the present invention provides a weldable polyethylene composition exhibiting good fillability, good HF weldability, good sealing strength, and good printability.
Claims
1. A crosslinkable polyethylene composition for high-frequency welding, comprising: - A copolymer (A) of ethylene and an α-olefin comonomer (A1) having 3 to 12 carbon atoms, with a density of 850 kg / m³. 3 Up to 970 kg / m 3 ,as well as - A terpolymer (B) of ethylene, a polar comonomer (B1), and a crosslinkable comonomer (B2), in, The amount of the polar comonomer (B1) in the ethylene terpolymer (B) is 25 wt% to 30 wt% relative to the total weight of the ethylene terpolymer (B).
2. The crosslinkable polyethylene composition according to claim 1, wherein, The α-olefin comonomer (A1) in the ethylene copolymer (A) has 4 to 10 carbon atoms.
3. The crosslinkable polyethylene composition according to claim 2, wherein, The α-olefin comonomer (A1) in the ethylene copolymer (A) has 7 to 9 carbon atoms.
4. The crosslinkable polyethylene composition according to claim 2, wherein, The α-olefin comonomer (A1) in the ethylene copolymer (A) is 1-octene.
5. The crosslinkable polyethylene composition according to claim 1, wherein, The density of the ethylene copolymer (A) is determined to be 860 kg / m³ according to ISO 1183-1:2004. 3 Up to 930 kg / m 3 Within the range.
6. The crosslinkable polyethylene composition according to claim 1, wherein, The MFR2 of the ethylene copolymer (A) was determined according to ISO 1133 at 190°C and 2.16 kg load to be in the range of 0.5 g / 10 min to 25 g / 10 min.
7. The crosslinkable polyethylene composition according to claim 1, wherein, The MFR2 of the ethylene terpolymer (B) was determined according to ISO 1133 at 190°C and 2.16 kg load to be in the range of 0.1 g / 10 min to 50 g / 10 min.
8. The crosslinkable polyethylene composition according to any one of claims 1 to 7, wherein, The polar comonomer (B1) in the ethylene terpolymer (B) is methyl acrylate.
9. The crosslinkable polyethylene composition according to any one of claims 1 to 7, wherein, The amount of the crosslinkable comonomer (B2) in the ethylene terpolymer (B) is from 0.1 wt% to 6 wt% relative to the total weight of the ethylene terpolymer (B).
10. The crosslinkable polyethylene composition according to any one of claims 1 to 7, wherein, The crosslinkable comonomer (B2) in the ethylene terpolymer (B) includes at least one hydrolyzable silane group.
11. The crosslinkable polyethylene composition according to claim 10, wherein, The at least one hydrolyzable silane group of the crosslinkable comonomer (B2) is represented by formula (I): R 1 SiR 2 q Y 3-q (I) Among them, R 1 It is an olefinic unsaturated hydrocarbon group, alkyloxy group, or (meth)acryloyloxy hydrocarbon group, each R 2 Independently, it is an aliphatic saturated hydrocarbon group, Y can be the same or different, is a hydrolyzable organic group, and q is taken from 0, 1 or 2.
12. The crosslinkable polyethylene composition according to any one of claims 1 to 7, wherein, The crosslinkable polyethylene composition further comprises a silanol condensation catalyst (C).
13. The crosslinkable polyethylene composition according to any one of claims 1 to 7, wherein, The sealing time is less than 7 seconds.
14. The crosslinkable polyethylene composition according to any one of claims 1 to 7, wherein, According to ISO 527-1, the sealing strength of the crosslinkable polyethylene composition is at least 1.0 N / mm. 2 .
15. Articles suitable for high-frequency welding, comprising the crosslinkable polyethylene composition as described in any one of claims 1 to 14, wherein, The product is a membrane or a seal.
16. Use of the crosslinkable polyethylene composition according to any one of claims 1 to 14 for high-frequency welding.
Citation Information
Patent Citations
Crosslinkable polyolefin compositions containing crystalline zeolites
EP0149782A2
Radio frequency energy sensitized compositions and method for sensitizing compositions to radio frequency energy
EP0193902A2
Polyethylene compatible sulphonic acids as silane crosslinking catalysts
EP0736065A1
Alkylaryl and arylalkyl monosulfonic acid catalysts for crosslinking polyethylene
EP1309631A1
Alkylated ARYL disulfonic acid catalysts for crosslinking polyethylene
EP1309632A1